Formulation and Evaluation of pH-Modulated Amorphous Solid Dispersion-Based Orodispersible Tablets of Cefdinir - Yahya Alhamhoom; Thanusha Kumaraswamy; Avichal Kumar; Shivakumar Hagalavadi Nanjappa; Sanjana S. Prakash; Mohamed Rahamathulla; Kamal Y. Thajudeen; Mohammed Muqtader Ahmed; Thippeswamy Boreddy Shivanandappa (MDPI AG, 2024)
Cefdinir (CEF) is a semi-synthetic third-generation broad-spectrum oral cephalosporin that exhibits poor solubility at lower pH values. Considering this, pH-modulated CEF solid dispersions (ASDs) were produced by solvent evaporation method employing various hydrophilic carriers and alkalizers. Among different carriers, ASDs produced using PEG 6000 with meglumine as alkalizer were found to significantly increase (p < 0.005) the drug solubility (4.50 ± 0.32 mg/mL) in pH 1.2. Fourier transform infrared spectrophotometry confirmed chemical integrity of CEF while differential scanning calorimetry (DSC) and X-ray diffractometry (XRD) indicated CEF was reduced to an amorphous state in ASD8. Antimicrobial assay performed by well diffusion method against Staphylococcus aureus (MTCC96) and Escherichia coli (MTCC118) demonstrated significantly superior (p < 0.001) efficacy of CEFSD compared to CEF. The porous orodispersible tablets (ODTs) of ASD8 (batch F5) were developed by incorporating ammonium bicarbonate as a subliming agent by direct compression, followed by vacuum drying displayed quick disintegration (27.11 ± 1.96 s) that met compendial norms and near-complete dissolution (93.85 ± 1.27%) in 30 min. The ODTs of ASD8 appear to be a promising platform to mitigate the pH-dependent solubility and dissolution issues associated with CEF in challenging physiological pH conditions prevalent in stomach. Thus, ODTs of ASD8 are likely to effectively manage various infections and avoid development of drug-resistant strains, thereby improving the curing rates.